Petrogenesis and tectonic evolution of tourmaline- bearing leucogranites, Sikait area, South Eastern Desert of Egypt utilizing mineralogical and bulk rock analysis - Gehad M. Saleh; Mohamed S. Kamar; Farrage M. Khaleal; Mokhles K. Azer; Taher Nasr; El Saeed R. Lasheen (Scientific Reports)
Abstract The current research discuss in detail the tourmaline distribution in Sikait leucogranites in order to deduce its genesis and type. We conduct new detailed geological, petrographical, mineralogical, and geochemical examinations to understand the Arabian Nubian Shield development by investigation of such the examined leucogranites. Tourmaline occurs as disseminated or cluster nodular within coarse-grained leucogranites. Geochemically, the examined leucogranites have high contents of SiO2 (69.44–75.87 wt%), and total alkalis (mean > 7) with low mean CaO (0.4 wt%), Fe2O3 (1.93 wt%), and Mg# (14.59) values. They share features of calc-alkaline, strongly peraluminous (A/CNK > 1.1), with high contents of Zn (av. 266.68 ppm), Pb (av. 29.13 ppm), Rb/Sr (av. 22), Al2O3/TiO2 (av. 832.6), FeO/MgO (av. 12.24). They are remarkably enriched in semi-volatile elements (Pb = 12–235 ppm), and LILEs (Rb = 192–679 ppm) relative to HFSEs (e.g. Zr, U and Nb) with notable strong Ba, Sr and Ti negative anomalies. They are depleted in ∑REEs (av. 19.1 ppm) and reveal parallel, uniform patterns slightly notable depletion of HREEs in comparison with LREEs. They reveal extreme pronounced Eu (av. Eu/Eu*= 0.02) negative and Ce/Ce* (0.76–1.12) positive anomalies. The examined rocks have prominent tetrad effect (M-type) as indicated by Irber and Lambda methods. Based up on conventional geochemical diagrams, the examined rocks are post-collisional S-type granites derived by partial degree of the clay-rich pelite rocks melting followed by extreme fractional crystallization processes during post-collisional extension episode at temperatures (663 –786 °C) based on saturation temperature of zircon. The investigated tourmaline nodules are of alkali group and foitite end-member.